2015
DOI: 10.1007/s00784-015-1629-7
|View full text |Cite
|
Sign up to set email alerts
|

Osseointegration of titanium implants with SLAffinity treatment: a histological and biomechanical study in miniature pigs

Abstract: The use of SLAffinity-Ti implants has potential for improvement of early osseointegration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 44 publications
1
10
0
1
Order By: Relevance
“…surfaces (Elias, Lima, Valiev, & Meyers, 2008). In previous studies, SLA implant surfaces were shown to achieve a high reverse torque resistance at earlier time points of the healing period (Abdel-Haq, Karabuda, Arisan, Mutlu, & Kurkcu, 2011; Ou et al, 2016). Findings in this study are also confirmatory, and an RTV of 73.5 N/cm was achieved in the SLA group at the 3rd week.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…surfaces (Elias, Lima, Valiev, & Meyers, 2008). In previous studies, SLA implant surfaces were shown to achieve a high reverse torque resistance at earlier time points of the healing period (Abdel-Haq, Karabuda, Arisan, Mutlu, & Kurkcu, 2011; Ou et al, 2016). Findings in this study are also confirmatory, and an RTV of 73.5 N/cm was achieved in the SLA group at the 3rd week.…”
Section: Discussionsupporting
confidence: 80%
“…Controlled unscrewing of the implant body until breakage of the bone‐implant interface (used as RTV in this study) is routinely used in the comparison of the osseointegration strength among different surfaces (Elias, Lima, Valiev, & Meyers, ). In previous studies, SLA implant surfaces were shown to achieve a high reverse torque resistance at earlier time points of the healing period (Abdel‐Haq, Karabuda, Arisan, Mutlu, & Kurkcu, ; Ou et al., ). Findings in this study are also confirmatory, and an RTV of 73.5 N/cm was achieved in the SLA group at the 3rd week.…”
Section: Discussionmentioning
confidence: 95%
“…The roughness surface of the Ti-implant was obtained by a sandblasting large-grit acid-etching (SLA) technique51. The samples were sterilized with cobalt-60 before the cell plating and animal studies.…”
Section: Methodsmentioning
confidence: 99%
“…In order to obtain micro/nanostructures, many methods have been tried, especially the combination of anodic oxidation and other methods, such as silver plasma immersion ion implantation (Ag-PIII) [23], sandblasting and acid-etching [24,25], and heat treatment [26]. It has been reported that the micro/nanocomposite surface obtained by the composite method could improve the antibacterial properties of the implant [23], the photocatalytic activity [24], the bone deposition [25], the cell response, and the apatite-forming ability [26].…”
Section: Introductionmentioning
confidence: 99%